Rola Ibizy w kontaktach handlowych w zachodniej części basenu Morza Śródziemnego w VII–III wieku p.n.e. - Belicki, Krzysztof (Rzym a Półwysep Iberyjski: Różnorodność relacji od starożytności po współczesność, 2019)
The aim of the paper is to determine the role of Ibiza in the Western Mediterranean, from the foundation of the first Phoenician settlement in the second half of the 7th century BC until the Roman conquest. In the first part of the article, I discuss the geographical characteristics of the Balearic Islands and the weather conditions on the Mediterranean Sea. The main analysis, based on selected historical and archaeological finds, primarily amphoras, has the objective of delineating the island’s economy and its place on commercial routes.